2016
DOI: 10.1016/j.ijid.2016.11.160
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in the Caribbean: A One Health approach

Abstract: ® . Results: The results of this work confirm that bovine brucellosis is endemic in Cameroon. With an uneven but wide distribution the study revealed a 4.61% and 16% seroprevalence at the animal-level and herd-level respectively. There was a preponderance of seropositivity in the GHS (87.5%) over the WHPS (12.5%). The extrinsic risk factors investigated were all positively correlated with seropositivity. It was interesting to note that cattle interactivity with sheep and goats (small ruminants), wildlife, her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Seroprevalence studies have reported higher seroprevalence values in Cameroon, including 9.2% (i-ELISA) from parts of the west and central regions [2], 3.4-5.9% (RBPT and i-ELISA, respectively) in cattle in Ngaoundere [17], 4.6% (RBPT) in the western highland savannah [16], and 5.2% (c-ELISA) in the northwest region [7]. Te higher prevalence in these regions could be attributed to agricultural practices, predominated by the rearing of livestock.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Seroprevalence studies have reported higher seroprevalence values in Cameroon, including 9.2% (i-ELISA) from parts of the west and central regions [2], 3.4-5.9% (RBPT and i-ELISA, respectively) in cattle in Ngaoundere [17], 4.6% (RBPT) in the western highland savannah [16], and 5.2% (c-ELISA) in the northwest region [7]. Te higher prevalence in these regions could be attributed to agricultural practices, predominated by the rearing of livestock.…”
Section: Discussionmentioning
confidence: 98%
“…Sporadic cases of cattle brucellosis are often reported in some sub-Saharan African countries, with prevalence reaching 41% in some areas [2,5,7]. Cattle brucellosis is endemic in Cameroon, with reported seroprevalence ranging from 2.3-30.8% [6,10,[12][13][14][15][16][17][18]. A recent study investigating brucellosis in domestic animals reported an overall seroprevalence of 6.4%.…”
Section: Introductionmentioning
confidence: 99%
“…These animals roam onto the airstrip and roads, constituting traffic hazards [55]. They have the potential to transmit zoonotic diseases and threaten biodiversity through the destruction of vegetation and other animals' habitats and are at risk for starvation in times of severe drought [56]. Efforts are needed to reduce animal populations and restrict their range.…”
Section: Challenges For Feral Livestockmentioning
confidence: 99%
“…Numerous national organizations, including the Center for Disease Control, United States Department of Agriculture, the American Medical Association, and also international agencies including EcoHealth Alliance and the World Health Organization, have adopted a One Health philosophy. It has been applied to a range of issues from the control of zoonotic disease [56,58] and disaster response [59,60] to addressing consequences of climate change [61]. The destruction of infrastructure that occurred on Barbuda during hurricane Irma coupled with the already fragile ecology of the island resulting from overgrazing, competition by feral animals, a water system at high risk of contamination and increasing salinity, and pressure from increasing tourism makes One Health a candidate platform upon which to rebuild.…”
Section: A One Health Approachmentioning
confidence: 99%